Irradiation resistance of thermo-optical properties of zirconium diboride by 3 MeV electrons - Rønning, Daniel; Tang, Yinglu (Frontiers in Space Technologies, 2024)
Due to good thermal conductivity and thermal shock resistance, ultra-high temperature ceramics (UHTCs) such as zirconium diboride (ZrB2) have been investigated as promising materials to be used in reusable thermal protection systems (TPS). TPSs are vital to the heat balance of a spacecraft during atmospheric reentry and subsequent operation in space. Hence, the thermal and optical properties are especially critical for such applications. Meanwhile, radiation exposure in space can pose risks of degrading such material properties, especially over a prolonged mission duration. The interaction of electron radiation-which can be found in the outer Van Allen belt, with ZrB2 has not been studied previously and was chosen as the main scope of this study. An electron source of 3MeV with different radiation exposure time was used. The response of thermo-optical properties of ZrB2 to increasing electron radiation fluences was investigated. ZrB2 samples were made through spark plasma sintering (SPS) into sintered pellets and then exposed to 3 MeV electron irradiation. These ZrB2 samples were characterized by their microstructure, thermal conductivity, coefficient of thermal expansion (CTE), emittance, absorptivity, and surface roughness before and after irradiation. It was found that ZrB2's thermo-optical properties showed high radiation resistance at these fluences, and no apparent microstructural change was observed after irradiation. However, the irradiated samples had, on average, a 29% lower surface roughness than the unirradiated samples, possibly originating from electron sputtering.